Evaluation of clinical and demographic profile of leprosy with special reference to WHO-fixed duration multidrug therapy non-responders: a cross-sectional analysis at a tertiary care centre in Maharashtra - Sahu, Monali; Belgaumkar, Vasudha; Chavan, Ravindranath B. (International Journal of Research in Dermatology, 2021)
Background: India remains one of the highest contributors to the global burden of leprosy despite declaring elimination in 2005 under National Leprosy Elimination Program (NLEP). The objective of this study was to document the clinical and socio-demographic profile of leprosy patients, determine the proportion suspected with inadequate/non-response to standard World Health Organisation (WHO)-Fixed duration multi drug therapy (FD-MDT) and identify contributory factors. Methods: A cross-sectional study was conducted on 123 leprosy patients over 2 months. Screened patients were categorised into suspected MDT non-responders (Group A, 21) and those not satisfying criteria (Group B, 102) for non-responders. Medical records were abstracted and patients subjected to detailed history and clinical examination. Results: Burden of WHO-MDT non-responders was 17 % (mean age 37.64 years).Majority were male in both groups. Borderline lepromatous (33%) and borderline tuberculoid (58%) were the predominant types in group A and B respectively. Among non-responders, male gender and grade 1disabilitywere significant associations, 17 were on extended-MDT;1 patient was prescribed second-line drugs,3 received both MDT and second-line drugs. More-than-half had relapsed within 5 years. Conclusions: This study highlights the need for customised-treatment in selective situations to minimise relapses. Determinants in WHO-FD-MDT non- responders/relapse cases were male gender, young adults, lower socioeconomic status, lepromatous form, disability, high initial bacteriological index, non-compliance and early relapses. Leprosy eradication can be facilitated by individually focused management strategies including judicious use of bacteriological index, counseling and long- term follow-up depending on the patient profile. Active surveillance and early detection of relapse may prevent further complications and decrease drug resistance.